The Effect Of Nutritional Management On Energy Levels In Pencak Silat Athletes - Daulay, Dicky Edwar; Keliat, Pedomanta (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2023)
Athletes are encouraged to balance their energy needs by consuming 55–65% carbohydrates, 20–35% fat, and 12–15% protein. The purpose of this study is to evaluate the association between food and energy sufficiency in Pencak Silat athletes at Bina Guna College of Sports and Health. This study included ten samples of active student athletes from UKM Pencak Silat at Bina Guna College of Sports and Health, aged 18 to 20. This is a qualitative study conducted using a case study design. All data on the degree of energy adequacy of these Pencak Silat athletes was obtained through characteristic interviews and questionnaires completed on a Google form with three 24-hour food recalls. Data collection includes eating habits, eating behaviour, food consumption over three days, exercise intensity, and diet that influences training. The results of the research analysis showed that nutritional status based on BMI ten athletes obtained 100% normal BMI, as well as the level of deficit energy adequacy as many as nine Pencak Silat athletes (90%) and one Pencak Silat athlete had a moderate level of energy adequacy (10%).